Three-Dimensional Modelling of Notched Connections for Timber–Concrete Composite Beams. Issue 2 (1st May 2017) - Bedon, Chiara; Fragiacomo, Massimo
Abstract: Notched connections are extensively used in timber–concrete (TC) composite beams and floors due to their typically high shear strength and stiffness. Several variables can affect their overall structural performance and failure mechanism, and their structural optimisation still represents an open issue. This paper presents an exploratory finite element (FE) numerical investigation carried out through advanced three-dimensional (3D) models, where a key role is assigned to several mechanical features. The typical non-linear behaviour of each component (the reinforced concrete topping, the steel coach screw, the timber beam) is implemented. Shear or crushing failure mechanisms in the concrete and possible yielding of the coach screw as well as failure mechanisms in the timber beam due to longitudinal shear or tension perpendicular to the grain can be taken into account via cohesive elements, material damage and surface-to-surface contact interactions. Based on a parametric study of TC connections with different geometrical properties, the FE results are compared with past short-term push-out experimental data taken from literature as well as with predictions of simplified analytical models available in literature. It is shown that the FE model is capable of capturing the behaviour of the notched connections, including the collapse load and the failure mechanisms.